Design of an automated rainwater harvesting system for urban agriculture - Loh, Yik Wei (2022)
Rainwater harvesting system (RWHS) is gaining attention as an alternative water source for agriculture worldwide as agricultural sector utilities approximately 70% of freshwater supply and is projected to increase by 20% from 2014 to 2040. This study is based in Klang Valley, Malaysia where water crises have been rampant throughout the years due to water pollution and flash floods. This has affected the freshwater supply in the country, led to a demand for RWHS. The average cost of installing a RWHS typically costs between RM 1,500 to RM 10,000 depending on their specifications and functionality. Although rainwater is a potential source for non-portable use, harvested rainwater for urban agriculture may require better quality monitoring and control. Without proper quality control, pollution in harvested rainwater may be a threat to crops, soil and human health in urban agriculture. Therefore, this project aims to propose a minimal viable design of an automated RWHS to support sustainable urban agriculture by reducing freshwater consumption and integrating quality control automation. The proposed system is equipped with a pH sensor, and a float sensor to monitor the water quality and level of rainwater harvested. Electrical conductivity was also tested physically in order to determine the water quality of rainwater harvested. The prototype proved that it is viable for urban agriculture use as with the aid of an automation system, it could harvest rainwater that meets the irrigation standard and also discharge unqualified rainwater. A comparative study of two different automated designs, first design - with a first flush diverter versus and second design - with a fine mesh filter were examined, and the results indicated that the fine mesh filter design showed greater potential in water and cost conservation as it could harvest a greater volume of rainwater. The total cost of the system with a first flush diverter in five years of operation is RM 6,634.45 whereas the system with a fine mesh filter is RM 6,634.45 and the payback period was 2.97 years and 3.37 years, respectively. Therefore, an automated RWHS with a first flush diverter was chosen as the viable design for urban agriculture as it could preserve better water quality of harvested rainwater and reduce the maintenance cost in the long run.